Variation Within Idiomatic Variation: Exploring the Differences Between Speakers and Idioms - Geeraert, Kristina; Newman, John; Baayen, R. Harald (Lesya Ukrainka Volyn National University, 2020)
Corpus-based research on idiomatic variation has shown that idioms can be utilized with an extensive range of variation, including the possibility of idioms occurring with adjectival modification (e.g. make rapid headway), lexical variation (e.g. the calm/lull before the storm), and partial forms (e.g. birds of a feather [flock together]). Previous experimental research eliciting variation within idioms has tended to focus on unintended ‘slips of the tongue’, or errors in production. To date, no experimental study has explored the creativity that speakers can employ when using idioms. This study, by contrast, aims to elicit conscious and spontaneous productions of idiomatic variation, exploring just how creative speakers can be when using idiomatic expressions. Participants were asked to create headlines for newspaper snippets using provided idioms. They were explicitly told that the expression did not have to be exact and that they could be as creative as they wanted. The headlines for each idiom and each speaker were then examined. Variational patterns are observed for both idioms and speakers. For instance, some idioms (e.g. jump on the bandwagon) typically occur with partial forms, lexical variation, and/or adjectival modification; whereas other idioms (e.g. call the shots) are predominantly used in their canonical form. Similarly, some speakers (e.g. Speaker 14037) demonstrated considerable flexibility and playfulness when using the expressions, while other speakers (e.g. Speaker 14020) preferred minimal, if any, modification to the idioms. These results not only converge with previous corpus-based findings, but they also highlight the individual differences between speakers, as well as reveal how creative and innovative speakers can be when using idiomatic expressions.
Keywords: idioms; idiomatic variation; creativity; experimental; person-oriented; English